2022
DOI: 10.1002/mp.16029
|View full text |Cite
|
Sign up to set email alerts
|

Modeling RBE with other quantities than LET significantly improves prediction of in vitro cell survival for proton therapy

Abstract: Background For proton therapy, a relative biological effectiveness (RBE) of 1.1 has broadly been applied clinically. However, as unexpected toxicities have been observed by the end of the proton tracks, variable RBE models have been proposed. Typically, the dose‐averaged linear energy transfer (LETd) has been used as an input variable for these models but the way the LETd was defined, calculated, or determined was not always consistent, potentially impacting the corresponding RBE value. Purpose This study comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…As Q eff was demonstrated to correlate better with the RBE than LET does (Kalholm et al 2022), these results suggest that not only the physical dose in light ion beams can be estimated with OSLDs but also the RBE-weighted dose. A detector with such capability might be helpful for 4 He-and 12 C-ion beam radiotherapy, as a variable RBE is used clinically.…”
Section: Dosimetry In 12 C-beamsmentioning
confidence: 76%
“…As Q eff was demonstrated to correlate better with the RBE than LET does (Kalholm et al 2022), these results suggest that not only the physical dose in light ion beams can be estimated with OSLDs but also the RBE-weighted dose. A detector with such capability might be helpful for 4 He-and 12 C-ion beam radiotherapy, as a variable RBE is used clinically.…”
Section: Dosimetry In 12 C-beamsmentioning
confidence: 76%
“…Furthermore, Kalholm et al (2023) demonstrated that in vitro cell survival in proton therapy was better modeled using radiation quality metrics other than LET. Similarly, for the response of OSLDs to light ion beams, neither LET f nor LET d were found to provide the most accurate description of the radiation fields (Christensen et al 2023).…”
Section: Let Averaging Challengesmentioning
confidence: 99%